Maqāṣid al-Sharī‘ah as an Ethical Framework for Artificial Intelligence Governance in Contemporary Muslim Societies - Nur Ali Yasin; Emha Dzia'ul Haq (Indonesian Journal of Sharia and Islamic Sciences, 2026)
Artificial intelligence (AI) has transformed decision-making across multiple sectors, creating ethical challenges that require governance frameworks beyond technical regulation. Contemporary AI governance emphasizes transparency, accountability, fairness, and privacy, yet these principles often lack normative foundations reflecting the ethical and legal values of Muslim societies. This study reconstructs Maqāṣid al-Sharī‘ah as an integrated ethical framework for AI governance in contemporary Muslim societies. Using a qualitative library research approach, the study synthesizes recent scholarship on Islamic jurisprudence, AI ethics, digital governance, and Maqāṣid al-Sharī‘ah through thematic and conceptual analysis. The findings indicate that the higher objectives of Islamic law provide a coherent governance framework by linking the preservation of religion, life, intellect, lineage, and wealth with AI governance principles, including transparency, explainability, accountability, human dignity, and public welfare. The framework also demonstrates the application of Maqāṣid al-Sharī‘ah across education, Islamic legal services, family law, digital communication, and Islamic finance. This study contributes by repositioning Maqāṣid al-Sharī‘ah as a multidimensional governance paradigm and providing a conceptual foundation for interdisciplinary research on Islamic ethics and responsible artificial intelligence governance.